Application and development of a TaqMan real-time PCR for detecting infectious spleen and kidney necrosis virus in Siniperca chuatsi. (June 2017) - Lin, Qiang; Fu, Xiaozhe; Liu, Lihui; Liang, Hongru; Guo, Huizhi; Yin, Shuwen; Kumaresan, Venkatesh; Huang, Zhibin; Li, Ningqiu
Abstract: Infectious spleen and kidney necrosis virus (ISKNV) is one of the major epidemiological agents that had caused great economic loss in Chinese perch ( Siniperca chuatsi ). In this study, a specific TaqMan real-time PCR was developed using a pair of primers and a TaqMan probe specific to the ORF007 gene of ISKNV to rapidly detect ISKNV copies in Chinese perch samples. This assay was optimized to produce linearity from 8.75 × 10 8 to 8.75 × 10 1 copies in standard curve with an efficiency of 98% and a R 2 value of 0.9999. Moreover, the minimum detection limit of this assay was 10, 000 times more sensitive than that of conventional PCR method. The coefficients of variation of intra- and inter-assay repeatability were less than 2.4% and 3.3%, respectively. The viral distribution in different tissues of diseased Chinese perch was evaluated by TaqMan real-time PCR method and the highest level of viral copies was detected in spleen. Among the 76 diseased Chinese perch clinical samples, 35 and 29 were positive samples based on the TaqMan real-time PCR and conventional PCR methods, respectively, indicating that the TaqMan real-time PCR was more sensitive than conventional PCR. Therefore, the TaqMan real-time PCR should be a useful tool for the early surveillance and quantitation of ISKNV. Highlights: A specific, sensitive, rapid, and quantitative Taqman real-time PCR for ISKNV detection was developed. The highest level of ISKNV viral copies was detected in spleen of Chinese perch. The Taqman real-time PCR can detect low-level ISKNV infection that can occur in apparently healthy Chinese perch.